Multiple criteria multivariant design of a building life cycle/Pastato gyvavimo proceso daugiakriterinis alternatyvusis projektavimas - Kvederytė, Artūras (Journal of Civil Engineering and Management, 2000)
A lot of data had to be processed and evaluated when carrying out multivariant design of a building life cycle. The number of feasible alternatives can be as large as 100,000. Each of the alternatives may be described from various perspectives, eg by conceptual and quantitative information. The problem arises how to perform computer-aided design of the alternative variants based on this enormous amount of information. To solve this problem a new method of multiple criteria multivariant building life cycle design was developed. According to the above method multiple criteria multivariant design is carried out in 5 stages (Fig 1). In order to reduce the amount of information being used in computer-aided multivariant design the codes of the alternative solutions are used. In this case, any i solution of j alternative is given aij code providing thorough quantitative (system of criteria, units of measure, significances, values, as well as a minimizing or maximizing criterion) and conceptual (text, drawings, graphics, video tapes) information about the alternative being considered (see Table 1). Thus, the use of codes of the alternative solutions in computer-aided multivariant design reduces the volume of information to be processed providing better insight into a physical meaning of computations. Codes, with conceptual and quantitative information provided, are used for describing all available alternative project solutions. The total number of these codes makes the table of codes of building life cycle alternatives more convenient for getting the alternative versions in a more simple way (see Table 1). As can be seen from Table 1, it contains c solutions of a building life cycle (plots, buildings, well-being, maintenance process, etc) of the ni alternative versions codes. Any i line of the code table represents the codes of Ai solution aij alternatives. If the information relating to the solutions in the code table of building life cycle alternatives is represented by codes, then the code contains quantitative and conceptual information (see Table 1). In this case, ni alternatives of any i solution are being considered in developing the alternative versions of a building life cycle. For example, if in determining possible building life cycle alternative versions 10 alternatives are considered for any of 10 solutions, then, according to equation 1 maximum ten billion such variants will be obtained. It is evident that in this and similar cases it is hardly possible and reasonable to analyse all the versions from various perspectives. Therefore, it is advisable to reduce their number as follows. If a project of c solutions having ni alternatives allows k combinations (Equation 1) then, by using multiple criteria analysis methods, pmost efficient versions should be chosen from every solution for further consideration (see Table 2). In this way, inefficient variants are being removed. The best solution alternatives obtained are then grouped according to priority considerations. In Table 2 ail is a code of the best variant of i solution, while aip is a code of its worst version. Then, project variants are being developed based on the efficient p alternatives of c solutions chosen. At the beginning, this process should involve the codes of the alternative solutions. The first building life cycle variant is obtained by analysing the best solution variants according to the priority order (see Table 2 and 3). The last variant is based on solution versions from the bottom of priority table, while intermediate variants are obtained with account of the versions found in the middle of this table. For example, the first building life cycle version is based on a11 plot, a21 building, ai1 well-being, ac1 maintenance, etc variants. The last building life cycle version takes into account a1p plot, a2p building, aip well-being, acp maintenance, etc variants. In this case, combinations are obtained by using p alternatives from any c solutions. While in Table 3 the development of building life cycle alternatives was based on codes of solution alternatives, Table 4 presents conceptual and quantitative information about the variants instead of the codes. When a particular building life cycle is being considered, the values relating to various solutions but based on the same criterion are recalculated into a single reduced value. After the reduction of the same criterion (eg cost, comfortability) values of various solutions (plot, building, well-being, maintenance) to a single one it is necessary to appraise significances of these solutions. For example, noise level within and outside the building is not of the same significance to its inhabitants. The same applies to paying the money (it depends on whether—this should be done at the present moment or in some years). The above significances of the solutions are determined by using expert, financial analysis and other methods. The significances should be made compatible in two directions: horizontally (among criteria) and vertically (among solutions). In this way, Table 4 may be transformed into a summary decision making table (see Table 5) containing all building life cycle versions and overall related information. A new method of multiple criteria multivariant design of a building life cycle enabling the user to make computer-aided design of up to 100,000 alternative project versions was developed. Any building life cycle variant obtained in this way is based on quantitative and conceptual information. Article in Lithuanian. First Published Online: 26 Jul 2012